IGF-1 Levels Among Adolescent Girls Living In Jakarta and It's relation to Nutritional Status - Maretha Primariayu; Ririn Hariani; Saptawati Bardosono; Noorwati Sutandyo (Indonesian Nutrition Association, 2018)
Background and Objective:Insulin-like growth factor (IGF)-1 is one of the hormones that plays a role in the growth of adolescent girls. Its level will rise at puberty and begin to decline at the end of puberty. High IGF-1 levels in adult is associated with the incidence of breast cancer. This study aims to know the level of IGF-1 and investigates its relationship with dietary intake, nutritional status, and physical activity of adolescent girls aged 13-15 in Jakarta.Methods and Study Design:This cross-sectional study used secondary data from a previous study (titled